The strategic state (primera de tres partes) - Paquet, Gilles (CIENCIA ergo-sum; Vol. 3 Núm. 3 (1996): CIENCIA ergo-sum (noviembre 1996-febrero 1997), 2017)
Canada, like many industrialized countries, is facing a crisis of the state. At a time when the new demands on the state are increasing, the old social technology appears to be inadequate. This calls for the definition of a new state. The paper identifies the guiding values and the design principies that are likely to underpin the social architecture of this new strategic state. It identifies also one features of the strategic state (meso\forums, network organizations, moral contracts) and the nature leadership in this new strategic state (leader as animateur and use language citizenship). It is argued that in the new strategic state economy, society and polity must share the organizational task and that the only viable agenda for the strategic state is a modest agenda promoting social learning and finding the path of mínimum regret are the only hopes that leaders may reasonably entertain.